Trade Role in Shaping Multicultural Society Aceh During Iskandar Muda Period - Monika Sari, Alya Wulan Nur Fatimah & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This study aims to determine: 1) socio-economic life period of Iskandar Muda. 2) The role oftrade in shaping the multicultural society of Aceh. This study uses qualitative research methodswith the historical approach. In the aspect of social life of contemporary Acehnese IskandarMuda is open to outside influence for these effects was not against the rules or traditions of thepeople of Aceh. In the economic aspect, the lives of the people of Aceh strongly influenced bytrading activity. At the time of Iskandar Muda, Aceh became an important trading port for localmerchants, regional and international levels. Trading activity is what causes the formation ofAceh multiethnic society, evidenced by the number of ethnic villages, among others: Arabsettlements (Pekojan), Javanese village, township Malay, Indian Village, etc. Thesecommunities live side by side so as to create a social harmony.Keyword : Aceh, multiculturalism, trade